2020
DOI: 10.1038/s41598-020-59172-3
|View full text |Cite
|
Sign up to set email alerts
|

High pressure inhibits signaling protein binding to the flagellar motor and bacterial chemotaxis through enhanced hydration

Abstract: In Escherichia coli, the binding of the chemotaxis signaling protein CheY to the flagellar motor protein FliM induces reversal of the motor rotation. Using molecular dynamics (MD) simulations and parallel cascade selection MD (PaCS-MD), we show that high pressure increases the water density in the first hydration shell of CheY and considerably induces water penetration into the CheY-FliM interface. PaCS-MD enabled us to observe pressure-induced dissociation of the CheY-FliM complex at atomic resolution. Pressu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 82 publications
(79 reference statements)
1
43
0
Order By: Relevance
“…The dissociation of protein/ligand complexes simulated using PaCS-MD [56] according to the procedure was described earlier [28]. Ten parallel MDs (replicas) were used for the trypsin/benzamine and FKBP/FK506 complexes and 30 replicas were employed for A2A/T4E.…”
Section: Simulation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The dissociation of protein/ligand complexes simulated using PaCS-MD [56] according to the procedure was described earlier [28]. Ten parallel MDs (replicas) were used for the trypsin/benzamine and FKBP/FK506 complexes and 30 replicas were employed for A2A/T4E.…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…PaCS-MD comprises cycles of multiple parallel short (typically 0.1 ns) MD simulations combined with initial structure selection. The repetition of parallel MD simulations from selected promising structures with regenerated initial atom velocities drastically enhances the probability of observing the dissociation of protein/ligand complexes by selecting snapshots with longer protein-ligand distances [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ikuro Kawagishi (Hosei University) showed that pressure affects bacterial chemotaxis. He demonstrated that high hydrostatic pressure can induce counter-clockwise rotation of the flagellar motor of Escherichia coli (Hata et al 2020a). Katsumi Imada (Osaka University) reported the molecular mechanisms of pressure-dependent fluorescence change of a yellow fluorescent protein mutated by the insertion of three glycine residues at β7 (YFP-3G) (Watanabe et al 2013).…”
mentioning
confidence: 99%
“…Katsumi Imada (Osaka University) reported the molecular mechanisms of pressure-dependent fluorescence change of a yellow fluorescent protein mutated by the insertion of three glycine residues at β7 (YFP-3G) (Watanabe et al 2013). Hiroaki Hata (Tokyo Institute of Technology) indicated that pressure enhanced hydration around proteins can inhibit the protein-protein interactions that play a key role in bacterial chemotaxis (Hata et al 2020a). In addition, Oleg Dobrokhotov (Nagoya University) showed that artificial induction of actomyosin-generated tension inhibits proliferation and promotes differentiation of keratinocyte carcinoma cells.…”
mentioning
confidence: 99%